Occurrence of Cryptosporidium parvum and Bacterial Pathogens in Faecal Material in the Red Fox (Vulpes vulpes) Population - Y. Nagano; M. B. Finn; C. J. Lowery; T. Murphy; J. Moriarty; E. Power; D. Toolan; A. O’Loughlin; M. Watabe; K. A. McCorry; E. Crothers; J. S. G. Dooley; et al. (Veterinary Research Communications, 2007)

Molecular and enzymatic properties of a cathepsin L-like proteinase with distinct substrate specificity from northern shrimp ( Pandalus borealis ) - H. Aoki; M. N. Ahsan; S. Watabe (Journal of Comparative Physiology B, 2004)

Primary structures and gene organizations of two types of Wap65 from the pufferfish Takifugu rubripes - M. Hirayama; M. Nakaniwa; D. Ikeda; N. Hirazawa; T. Otaka; T. Mitsuboshi; K. Shirasu; S. Watabe (Fish Physiology and Biochemistry, 2003)

Changes in mitochondrial fatty acid composition following temperature acclimation of carp and their possible effects on FoF1-ATPase activity - S. Itoi; S. Kawahara; H. Kondo; T. Sakai; S. Watabe (Fish Physiology and Biochemistry, 2003)

Production of recombinant goldfish gonadotropins by baculovirus in silkworm larvae - M. Kobayashi; T. Morita; K. Ikeguchi; G. Yoshizaki; T. Suzuki; S. Watabe (Fish Physiology and Biochemistry, 2003)

cDNA cloning and characterization of the warm-temperature-acclimation-associated protein Wap65 from carp, Cyprinus carpio - S. Kinoshita; S. Itoi; S. Watabe (Fish Physiology and Biochemistry, 2001)

Myogenic regulatory factors and muscle differentiation during ontogeny in fish - S. Watabe (Journal of Fish Biology, 1999)
cDNA clones encoding the myogenic regulatory factors, myogenin, MyoD and myf‐5 were cloned by reverse‐transcription polymerase chain reaction from larvae and embryos of the common carp. MEF2 cDNAs were also identified from an adult carp cDNA library. During the period of somite formation for carp, myf‐5 was the first factor to be expressed followed by MEF2C and MyoD, then myogenin and MEF2A, and finally skeletal myosin heavy chain and α‐actin. This study also examined, by Northern blot analysis, the accumulated mRNA levels of myosin heavy chain (MyHC) isoforms in carp fast skeletal muscle during water temperature acclimation from 20 to 30°C in relation to those of MyoD family and MEF2 family members. There was a dramatic decrease in the transcripts of the MyHC isoform predominantly expressed in cold‐acclimated carp and a significant increase in the transcripts of the MyHC isoform predominantly expressed in warm‐acclimated carp. Over the same acclimation period, the transcription levels of myogenin, MEF2A and MEF2C changed significantly, whereas MyoD transcripts were rather constant. The possible roles of MRFs and related transcription factors in muscle differentiation of fish are discussed.

The Wap65 gene expression of goldfish (Carassius auratus) in association with warm water temperature as well as bacterial lipopolysaccharide (LPS) - K. Kikuchi; S. Watabe; K. Aida (Fish Physiology and Biochemistry, 1997)